Comparison of Wound-bed Preparation Time in Chronic Traumatic Wound Using Topical Honey Application and Conventional Dressing - Mukarramah, Dewi A.; Sudjatmiko, Gentur (Jurnal Plastik Rekonstruksi, 2012)
Background: Prior to the de!nitive closure of wound by skin graft, it is essential for the recipient wound to be prepared adequately. Honey has been shown to exert a valuable effect in wound healing, atributale to its six favorable characteristics. This clinical study is proposed to determine the effectiveness of a specific sample honey (Madu Nusantara®) in accelarating the time of wound bed preparation in chronic traumatic wound.Methods: A randomized non-blinded clinical trial was done on patients with chronic traumatic wound who required wound bed preparation before definitive closure, during a one-year period. A total of 18 patients were included in the study, divided into two interventions. One has wound treated by topical application of honey (HDR), and controls were treated by conventional dressing (CDR). Daily wound treatment and evaluation was done using The Bates-Jensen Wound Assesment Tool until wound-bed was ready to be skin-grafted. The time required until wounds were ready to be grafted was also measured in both groups.Results: The mean time of wound bed preparation in HDR gorup was 12 days (n=11), and 26 days in CDR group(n=7, p 0.0055). The mean Bates-Jensen score of HDR improved from 45.45 before treatment to 23.36, versus 44.00 to 29.00 in CDR subjects.Conclusion: A favorable wound bed is essential prior to skin grafting.Our data shows that topical application of honey is more effective in accelerating the time of wound bed preparation than conventional dressing in patients with chronic traumatic wound.